Professional Lecturer and Institution Development: The role of goal-oriented inspiring interaction - Agus Kristiadi, Al.; Silitonga, Parlagutan; Achmadi, Rudhi (Universitas Ahmad Dahlan, 2025)
This study aims to accelerate and improve the accreditation status of Tourism Higher Education (THE). The research method uses quantitative methods. There were 92 respondents from 23 THE by saturated sampling techniques. The instrument used is a Questionnaire with a Likert scale of 1 to 7. The analysis method using SEM-PLS with Smart PLS 3.0 as a quantitative method and complemented by a Forum Group Discussion as a qualitative method to gain a more comprehensive perspective result. The results showed that the Top Management of THE must give challenging goals and targets to all lecturers so there are no asymmetric goals and targets. The common goal and targets start from publication in reputable international journals by lecturers with financial support and monitoring by the top management. Those lecturers who received top management support enabled lecturers to achieve position levels from expert assistants to head lectors (Associate professors). These achievements accelerate the chance of attaining THE accreditation status from the better to the best or superior. This research significantly contributes to the body of knowledge as lecturers are induced to have innovative Behavior. On the other hand, the management of institutions should adopt Goal-oriented, Inspiring Interaction rooted in goal-setting theory.